Development of Elite Mother Palms from the Best-Performing Slow-Vertical-Growth Oil Palm (Elaeis guineensis Jacq.) Genotypes - Anitha Pedapati; Kancherla Suresh; Ravi Kumar Mathur; Govindan Ravichandran; Prathapani Naveen Kumar; Hosahalli Parvathappa Bhagya; Banisetti Kalyana Babu; Kariyappa Sankar Narayana (Agriculture)
Harvesting is a serious issue in oil palm plantations after 15–20 years owing to the increased height of the trees (>9 m). The slow vertical growth of the oil palm dura genotypes is desired for increasing the D × P progenies’ productivity and economic life span upto ten years. A reduced height increment has a long-term impact on harvesting costs. The current study assessed 308 genotypes generated from African germplasm. Over a three year period, the biometric properties of eleven D × D crosses were evaluated in order to quantify genetic parameters and phenotypic correlations, and principal component analysis was performed for genetic attributes of the better-performing dwarf progenies in terms of yield. The evaluated genotypes have a highly significant influence (p < 0.01) on the majority of characteristics. The progenies yielded between 165 and 208 kg of fresh fruit bunches (FFBs) per palm every year. The height increment (HI) varied between 17% and 19%, with an overall average of 18%. Genotypes G8, G300, and G221 had the lowest yearly height increments, measuring 28.98, 29.19, and 30.87 cm, respectively. The outcome of the present study shows that they are slow-height-increment genotypes with a high FFB yield (>25 T/Ha). The creation of dura parents with a slow height increment in combination with a high bunch weight helps for prolonging the productive life of the palm to more than 35 years, adding value to obtain distinct oil palm varieties. Overall, this targeted breeding effort towards developing dwarf oil palm hybrids reflects a strategic approach to addressing specific challenges in oil palm cultivation, ultimately helping to promote the oil palm sector globally.